Farmers Utilization of Climate Change Adaptation Strategies Across Selected Agro-Ecological Zones in Nigeria - Olufunmilayo Grace Adenaiye; Simeon Dada yomi Alfred; Oluwatosin Oluwasegun Fasina (Turkish Journal of Agriculture: Food Science and Technology, 2021)
This study examined farmers’ level of use of climate change adaptation strategies across selected agro-ecological zones in Nigeria. Edo and Ondo States were selected for the study with three major agro-ecological zones. A multi-stage sampling procedure was used. The correlation analysis revealed a significant relationship between year of education and level of use of adaptation strategies (r = 0.15, P = 0.02). The result of Analysis of Variance (ANOVA) revealed that significant differences existed in most of the adaptation strategies employed except planting different varieties (F = 1.672, P = 0.190), intercropping (F = 0.646, P = 0.525), crop rotation (F = 2.436, P = 0.090) and migration to different sites (F = 0.661, P = 0.517). The study recommended that the issue of climate change should not be taken lightly by all stakeholders as its effect differs among various agro-ecological zones.